Immunomodulatory Effects of Probiotics on Th17-Mediated Immune Responses in Psoriasis: A Systematic Review and Meta-Analysis - Rindi Rosalina Fadly; Usman Pato; Maya Savira (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Psoriasis is a chronic inflammatory skin disorder with increasing evidence supporting the role of the gut-skin axis in its pathogenesis. Recent studies suggest that probiotic supplementation may modulate Th17-mediated immune responses and improve clinical outcomes in psoriasis. Methods: A systematic review and random-effects meta-analysis was conducted using PubMed, Scopus, Web of Science, and Cochrane Library databases (through February 2025). Randomised controlled trials evaluating probiotic supplementation in adult patients with psoriasis were included. The primary outcome was change in Psoriasis Area and Severity Index (PASI) score. Secondary outcomes included inflammatory markers (IL-6, CRP, IL-17) and immunological markers (Foxp3+ regulatory T cells, IL-10, TGF-β). Risk of bias was assessed using the Cochrane Risk of Bias tool (RoB 2), and evidence quality was evaluated using GRADE methodology. Results: Five randomised controlled trials encompassing 268 participants (132 intervention, 136 control) were analysed. The pooled effect size for clinical outcomes (PASI) showed significant improvement favouring probiotic supplementation (Hedges' g = −0.8165; 95% confidence interval [CI], −1.6487 to −0.0483; p = 0.048; I² = 92.45%). Substantial heterogeneity was observed, with the Alshihmani 2025 pilot study demonstrating markedly larger effects on immunological markers (Hedges' g = −5.6963). Subgroup analysis revealed single-strain probiotics (pooled Hedges' g = −0.3487) had smaller effect sizes than multi-strain formulations (pooled Hedges' g = −3.6740). Publication bias assessment via funnel plot and Egger's regression showed no statistically significant asymmetry (p = 0.087). Conclusion: Probiotic supplementation demonstrated statistically significant improvements in clinical outcomes and immunological markers in psoriasis. However, substantial heterogeneity and reliance on small trials limit certainty. The mechanistic evidence supporting gut-skin axis modulation warrants further investigation in adequately powered, long-term randomised controlled trials with standardised outcome measures and strain-specific analysis.